(untitled) (American Journal of Islam and Society, 2006)
In her book, Reina Lewis discusses how to acquire an accurate understanding of the various strands of neo-Orientalism that perpetuate long-lasting and contemporary stereotypes of Muslim women from traditional Islamic societies. Within the context of the current global and geopolitical landscape as well as the alleged American war on terror, the competing western imperialist and orientalist images, along with negative stereotypes, that characterize Muslim women are rhetorical. According to Lewis, all of these elements are at the center of knowledge that is produced and reproduced. This book focuses on Ottoman women’s writing from the beginning of the twentieth century and traces their “travel accounts, memories, and fractions that reveal a gendered counter-discourse that challenges Occidental stereotypes” (p. 1). The author’s main theme is how these writings not only challenged western Orientalist discourses, but also intervened in the Ottoman debate about women and national emancipation. The book, which follows an interdisciplinary approach, is divided into six chapters. In her introduction, Lewis argues that postcolonial studies have been too paradigmatic and narrow to include Middle Eastern and particularly Turkish experiences, since most postcolonial theories focus on the South Asian experience. Her novel endeavor helps bridge this void in postcolonial studies. Also, she introduces “to postcolonial studies the specificities of the late Ottoman situation and bringing to the reading of Ottoman sources the critical perspectives of postcolonial and gender theory” (p. 5). Moreover, she brings to light some western women’s writings, such as those of Grace Ellison and Lady Mary Wortley, who traveled to the East exploring the status of Middle Eastern women and, through their writings, tried to “challenge Western misapprehensions” of their status (p. 45) ...